2011
DOI: 10.3109/13625187.2011.631622
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-attitude-practice survey among Portuguese gynaecologists regarding combined hormonal contraceptives methods

Abstract: Objectives To evaluate knowledge, attitude and practices of Portuguese gynaecologists regarding combined hormonal contraceptives. Methods A cross-sectional survey was conducted among 303 gynaecologists. Results Ninety percent of the gynaecologists considered that deciding on contraceptive methods is a process wherein the woman has her say. Efficacy, safety and the woman's preference were the major factors influencing gynaecologists, while efficacy, tolerability and ease of use were the major factors percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
0
11
0
4
Order By: Relevance
“…These findings are in the same line with Vincent. [29] On the contrary, Bombas et al, [30] who reported that nurses' attitudes in their study showed least significant improvement and added there were difficulties in changing attitudes.…”
Section: Discussionmentioning
confidence: 74%
“…These findings are in the same line with Vincent. [29] On the contrary, Bombas et al, [30] who reported that nurses' attitudes in their study showed least significant improvement and added there were difficulties in changing attitudes.…”
Section: Discussionmentioning
confidence: 74%
“…1 School-based sexuality education similarly focuses on the harms versus the pleasures of sex (Connell, 2009;Goldman, 2008), especially for girls and young women (Fine, 1988). Clinically, care providers may lack both tools and time to discuss sexual issues with patients (Akers, Gold, Borrero, Santucci, & Schwarz, 2010;Bombas et al, 2012), and providers may be especially unlikely to inquire about sexuality in relationship to new contraceptive methods (versus, say, menopause) (Kottmel, Ruether-Wolf, & Bitzer, 2014). Public health programs and policies can also both reflect and perpetuate dominant gendered assumptions about women's sexuality-for example, with female condom programs focusing on reproductive health outcomes versus sexual rights (Peters, van Driel, & Jansen, 2013), or with adolescent pregnancy prevention policies that emphasize "sex is not for fun" and that young women should be sexually uninterested (Goicolea, Wulff, Sebastian, & Öhman, 2010).…”
mentioning
confidence: 99%
“…Such activities thereby improved their TENS information levels, resulting in the formation of additional TENS-related positive perceptions; findings that are in line with Vincent. 15 However, Bombas et al, 16 in their study, found nurses' perceptions showed very little positive improvement; the researchers encountered difficulties in changing the participant nurses' perceptions. In general, the OB nurses within the current study at first registered poor TENSrelated information scores, with high levels of negative perceptions.…”
Section: Discussionmentioning
confidence: 96%